26. 2x^2 +4x -10 = 0 (-4 + - (root(4^2 - 4*2*-10)))/2*2 =
(-4 + - (root(96)))/4
(-4 + (root(96)))/4 ≈ 1.45
(-4 - (root(96)))/4 ≈ -3.45
27. f(x) = 0 when any of the components that multiply together equal 0 for this function therefore x -2 = 0 x +3 = 0 x -5 = 0 so f(x) = 0 when x = 2, -3 or 5
28. It looks like it shows you how to do it
Answer:
Step-by-step explanation:
12x −3y=36 ⇔ 3y = 12x - 36
y = 4x - 12
y = 0 ⇔ 4x - 12 = 0 ⇔ 4x = 12 ⇔ x = 12/4 = 3
So (0 ; - 12) and (3 ; 0)
x/5 = 6/15
15x = 30
x = 2
answer
x = 2 ft
y/10 = 6/15
15y = 60
y = 4
answer
y = 4 ft